Ten tips for teaching research integrity to early career students: A perspective over 20 years - Martinez-Campos, Maruxa (Frontiers in Research Metrics and Analytics, 2022)
Early Career Researchers (ECRs) are becoming increasingly aware of the importance of good scientific practices to ensure their work is trustworthy; but also of the effect that research culture has on those practices. Here I suggest ten tips on how to best teach young researchers by incorporating their perspectives and needs. These are based on the lessons learned through our 20-year experience with a blended compulsory course for PhD students in a public university in Barcelona.